EVALUATION OF THE EFFECTS OF MONACOLIN K ON LIPID PROFILE AND ARTERIAL FUNCTION IN DYSLIPIDEMIC PATIENTS. (June 2018) - Castelnuovo, S.; Bosisio, R.; Pavanello, C.; Vallerio, P.; Maloberti, A.; D'Angelo, L.; Triglione, N.; Montero, B. Lopez; Giupponi, L.; Piccinelli, E.; Bassi, I.; Panzeri, F.; et al.
Abstract : Objective: dyslipidemia is the major Cardio-Vascular (CV) risk factor after hypertension. Some natural derivative molecules are able to improve the lipid profile, including monocolin K. This substance, which inhibits cholesterol synthesis, is produced by the fermentation of the red rice by a mycetes (Monascus Purpureus). Monacolin K is also known as lovastatin, but recent data show that compared to classic lovastatin, monacolin K would have a higher bioavailability, a greater efficacy at the same dosage and a satisfactory tolerability. Its role as an hypolipidemic therapy is accounted in guidelines but, to date, the effect on arterial functional and structural parameters has never been evaluated. Design and method: we evaluated 20 patients (11 females) with mild to moderate dyslipidemia (LDL cholesterol between 100–160 mg/dL) before and after three months from monacolin therapy starting. Obesity, hypertension (defined as BP values > 140/90 mmHg or anti-hypertensive therapy) and alterate glycemic state Inclusione criteria were Patients were non-obese, normotensive and normoglycemic. Serum lipids, Blood Pressure (BP) and Pulse Wave Velocity (PWV – Complior). Results: at baseline mean age was 43.4 ± 10.2, BP 121 ± 14/76 ± 9.3 and Heart Rate (HR) 67.2 ± 7.6. Treatment lead to a significant reduction of total and LDL cholesterol (total: 258.4 ± 25.9 versus 228.5 ± 28.4 mg/dL after 3 months, p < 0.001; LDL: 167.3 ± 31.2 versus 140.8 ± 25.2 mg/dL after 3 months, p < 0.001) and a significant improvement of arterial stiffness (PWV: 8.0 ± 1.4 versus 7.6 ± 1.2 m/s after 3 months, p = 0.02). No significant differences were seen for Systolic BP (121 ± 14 versus 118.3 ± 15.5 mmHg after 3 months, p = ns) and HR (67.2 ± 7.6 vs 69 ± 5.1 bpm after 3 months, p = ns) while a slight improvement for Diastolic BP (76 ± 9.3 vs 72.8 ± 8.3 mmHg after 3 months, p = 0, 004) was found. Conclusions: the results of the present study confirm that the treatment with monacolin K reduces significantly the levels of total and LDL cholesterol. They also show that a so brief treatment course of only 3 months induces an improvement in arterial function as showed by the reduction in pulse wave velocity without changes in BP and HR.